PENGETAHUAN LOKAL MASYARAKAT DALAM PENGELOLAAN PEKARANGAN DAN TEGALAN DI PERBUKITAN MENOREH KABUPATEN KULON PROGO - , Budi, Prof. Dr. Ir. San Afri Awang, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Privately owned forest in mostly village of Java is built upon homegarden and dry-field land. Homegarden and dry-field are two common terminologies, has been exist for a long time periods and still found until nowadays, including at community who live in Menoreh Hill of Kulon Progo District. The existence of those types of land which still managed indicates an ability of community to agree with various changes during their lifetime. This ability is predicted because of local knowledge owned by the community in the area. Research is aimed to study deeply and to construct local knowledge of homegarden and dry-field management doing by community of Menoreh Hill, Kulon Progo District. Method used in this research is phenomenology, conducted at Menoreh Hill of Kulon Pogo District for six months. Villages are selected by multistage sampling base on different height above sea level, that is low area (<300 asl in Giripeni and Bumirejo village), middle area (300-600 asl in Giripurwo and Hargotirto village) and hill area (>600 asl in Purwosari and Jatimulyo village). Data are collected through interview with snowball model, field observation and documents study which are analyzed by tabulation technique and phenomenology analysis descriptively. Homegarden and dry-field land in low area are managed by the community extensively, most species grow naturally and only small part are planted, main species produce fruits, wood for timber and energy, grass for livestock and cultivated small-scale of cow. Its products are used to complement and to add yields from paddy field. In middle area, community manage homegarden and dryfield land intensively, most plant and tree species are planted, grown and cultivated, main species produce fruits, wood for timber and energy, medicinal plant, grass and fodder, seasonal crops as food function, coconut sugar made from sap of coconut and also cultivated cow and local goat species. In hill area, community manage homegarden and dry-field land intensively with main species produce fruits, wood for timber and energy, medicinal plant, fodder, coconut sugar and also cultivated PE goat species. The yields of those tree, plant and livestock in middle and hill area are used as main source of income to meet their need. Those management of homegarden and dry-field land are resulted by local knowledge which is formed in Kebun Campur (Mixed Garden) that categorized as knowledge and scientific knowledge in system knowledge consisting input, process, output and outcome. Kebun Campur is also a result of social construction created by community in research area through dialectic process (internalization, objectivation, externalization) in their intersubjective world.